Active Learning dalam Pembelajaran PAI: Upaya Meningkatkan Keterlibatan Peserta Didik - Gilang Syahril Akbar; Sagita Ardiningrum; Givan Muhammad Nur Islami; Masliyah (Prodi Pendidikan Agama Islam, Institut KH. Ahmad Sanusi Sukabumi, 2025)
Active Learning is a learning approach that emphasizes students’ active participation through activities that encourage critical thinking, interaction, and problem-solving. In the context of Islamic Religious Education (PAI), this approach is expected to enhance students’ cognitive, affective, and psychomotor engagement. This study aims to analyze the influence of the Active Learning approach on student engagement in PAI learning. The study employed a quantitative approach using a survey method. Data were collected through closed-ended questionnaires and analyzed using simple linear regression and t-tests. The findings revealed that the implementation of the Active Learning approach had a positive and significant effect on student engagement in PAI learning. These findings indicate that active and participatory learning can enhance student engagement in the learning process. The results of this study reinforce the importance of implementing Active Learning-based instructional strategies as an effort to improve the quality of students’ cognitive, affective, and psychomotor engagement in Islamic Religious Education learning.